Predictors of Flares in Infliximab-treated Children With Inflammatory Bowel Disease. Issue 3 (25th September 2019) - Chabot, Caroline; Le Berre, Catherine; Baumann, Cédric; Remen, Thomas; De Carvalho Bittencourt, Marcelo; Danese, Silvio; Mercier, Clémence; Peyrin-Biroulet, Laurent; Bonneton, Marjorie
Abstract: One third of pediatric IBD patients who initially respond to infliximab (IFX) lose that response over time. This retrospective study, including 62 children treated with IFX from 2004 to 2017, aimed to identify factors associated with clinical flare. Ulcerative colitis, extreme body mass index, and lowest IFX trough levels were associated with clinical flare in the whole population. In Crohn disease patients, perianal disease was pejorative, while location proximal to ligament of Treitz was protective. Underweight patients probably correspond to the most severe cases who are more likely to relapse, with hypoalbuminemia responsible for lower systemic IFX availability. Obesity probably induces higher IFX clearance. Lay Summary: Assuring ongoing response to effective therapy is a critical treatment goal. This pediatric study identified patient and disease characteristics that can help flag which patients require the most careful monitoring of the dosing of their anti-TNF therapy to guarantee success.